Associations of state body images, physical self-descriptions, and body mass index - Stefano Scarpa (Formazione & Insegnamento, 2021)
Objectives: To find any possible relationships between dimensions of state body image (SBI), physical self-description (PSD) and body mass index (BMI). Methods: Body Image States Scale (BISS) and Physical Self-Description Questionnaire (PSDQ) were administrated to 280 students (143 girls and 137 boys) aged between 14 and 18 years (M = 16.86; SD = 1.28). Participants answered also a demographic form. Written informed consent was obtained from all participants and their parents.The study was based on a cross-sectional research design. Appropriate statistical analyzes (such as the correlation circle) were conducted on the data to verify the hypotheses of the study. Results: Pearson’s r correlations and the correlation circle have shown multiple correlations between variables, some of which have been very strong and significant (r closed to 1; p<.0001), so much so that areas of overlap between survey instruments could be identified. Conclusions: Possible areas of overlap between the questionnaires that measure the dimensions of the SBI and those of the PSD, and also BMI have been identified (e.g., appearance BISS – appearance PSDQ; obesity BISS – obesity PSDQ – BMI).